Enhancing speaking skills of Indonesian language at Thomas Carr College: An experience of the Indonesian teaching assistantship program in Australia - kholifah, siti; Ari Kusmiatun; Sugarti Febrinaldi, Sugarti Febrinaldi (COPE: Caraka Olah Pikir Edukatif, 2025)
This study explores the effectiveness of personalized tutoring methods in enhancing speaking skills among students of Thomas Carr College, particularly in preparing for the VCE Indonesian language exam. The main goal of this research is to assess how tailored lesson plans and one-on-one tutoring contribute to improving fluency, confidence, and critical thinking in spoken Indonesian. Utilizing a descriptive qualitative method, the study employs observation, feedback, and interaction analysis to evaluate the students’ performance. The findings reveal that individualized tutoring significantly boosts students’ conversational abilities, making them more confident in their oral examinations. Additionally, the study highlights the value of incorporating culturally relevant materials and real-life scenarios into language instruction, which enhances students’ connection to the language and its practical applications. This research emphasizes the role of teaching assistants in bridging language gaps and providing an immersive learning experience.